Fungsi Mamözi Göndra pada Pesta Perkawinan di Masyarakat Nias Bukit Gado Gado Kota Padang - Andreas Anugrah; Harisnal Hadi (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
This study aims to describe the Function of Mamözi Göndra Marriage Party in the Nias Bukit Gado Gado Community, Padang City by using a qualitative research method with a descriptive analysis approach. Stationery and camera supporting instruments. Data collection techniques are carried out by means of literature study, observation, interviews and documentation. The steps to analyze data are collecting data in the field, identifying data, clarifying data based on its type, and describing data. The object of this research is the Art of the Nias Community and this research shows how the Function of Mamözi Göndra in the Nias Community of Bukit Gado Gado which is displayed in the wedding party event. The results of the research on the function of Mamὃzi Gὃndra in the wedding party found that in terms of artistic form, Mamözi Göndra accompanies the Nias traditional dance offerings, entertainment and ceremonies which use Göndra, Faritia and Aramba as musical instruments and the lyrics used during the Maena Dance entitled Maena Ni Sikhi. Mamözi Göndra flourished at the Mendrofa Padang Big Family Ikatan Studio with the artist Yamohana Onelius Mendrofa. The Mendrofa Padang Big Family Association Studio is one of the studios in the Bukit Gado Gado area. Mamözi Göndra became the culture of the Nias people in Bukit Gado Gado.